Problem-Solving Design: Reasoning about Computational Value, Tradeoffs, and Resources - Horvitz, Eric (Proceedings of the NASA Research Forum. Mountain View, CA, 1987, 1987)
Several areas of research on problem-solving tradeoffs in reasoning systems are presented. Issues surrouding the valuation of computation in the context of computational resource constraints are introduced. Areas of research on problem-solving tradeoffs receiving ongoing attention include: (1) strategic control, (2) structural control, and (3) the explanation of computation. In each area, we review the application of utility theory to the task of controlling problem-solving tradeoffs.